The Terminator [videorecording (DVD)] - Cameron, James, 1954-; Cameron, James, 1954-; Schwarzenegger, Arnold; Hamilton, Linda, 1956-; Biehn, Michael, 1956-; Winfield, Paul; Henriksen, Lance, 1940-; Paxton, Bill (MGM Home Entertainment, 2001)
In 2029, giant super-computers dominate the planet and to destroy man's future by changing the past, they send an indestructible cyborg, a Terminator, back in time to kill a woman whose unborn son will become mankind's only hope. Can Sarah Connor protect herself from this unstoppable menace?